Psychometric Properties of the Bermond–Vorst Alexithymia Questionnaire (BVAQ) in the General Population and a Clinical Population - de Vroege, Lars; Emons, Wilco H. M.; Sijtsma, Klaas; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2018)
Introduction The Bermond-Vorst Alexithymia Questionnaire (BVAQ) has been validated in student samples and small clinical samples but not in the general population; thus, representative general-population norms are lacking. Aim We examined the factor structure of the BVAQ in Longitudinal Internet Studies for the Social Sciences panel data from the Dutch general population (N = 974). Results Factor analyses revealed a first-order five-factor model and a second-order two-factor model. However, in the second-order model, the factor interpreted as analyzing ability loaded on both the affective factor and the cognitive factor. Further analyses showed that the first-order test scores are more reliable than the second-order test scores. External and construct validity was addressed by comparing BVAQ scores with a clinical sample of patients suffering from somatic symptom and related disorder (SSRD) (N = 235). BVAQ scores differed significantly between the general population and patients suffering from SSRD, suggesting acceptable construct validity. Age was positively associated with alexithymia. Males showed higher levels of alexithymia. Discussion The BVAQ is a reliable alternative measure for measuring alexithymia.